Management of power states in a portable computing device - BRIDGWATER THOMAS; REES WILLIAM; COUSINEAU PAUL (2012)
Embodiments of the present invention provide a method and apparatus for managing power states in a personal computing device, while maintaining a perception by the user of instant on functionality. In various embodiments of the invention, the power states are presented to the user as a simple on/off option and the power management protocol is not visible within the user interface of the personal computing device thereby providing the user with the impression that the system is operating with a simple binary on/off protocol. In one embodiment of the invention, the personal computing device is operable to transition between a set of power states that include: 1) an on power state wherein the display is on and the customer can use all input devices; 2) a ready state wherein the display is turned off, but some modules, such as a radio module, remain on; 3) an off state wherein the personal computing device turns off after a slight pause, but a booted kernel is held in SDRAM; and 4) a dead state wherein none of the modules of the personal computing device are powered and the device must be cold booted to restart.